Rwanda: Ending hunger and undernutrition: challenges and opportunities - Compact2025 (International Food Policy Research Institute, 2017)
This scoping report was prepared to inform the Compact2025 roundtable discussion by providing an overview of the food security and nutrition challenges and opportunities in Rwanda. It includes the current food security and nutrition policy landscape across key sectors and actors in Rwanda as well as critical knowledge, policy, and implementation gaps. Additionally, the scoping report presents a SWOTanalysis (strengths, weaknesses, opportunities, and threats) that crystallizes the main elements that drive or hamper food security and nutrition in the country. To determine what is holding back progress, this report identifies several key research and action gaps, including the need for better coordination both horizontally (within and across ministries, donors, and other actors) and vertically (across tiers of government down to community-level implementation); continued investment in agricultural research and development (R&D) and innovation; and improved targeting and coverage of food security and nutrition actions.